2018
DOI: 10.21786/bbrc/11.4/25
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Aloe vera extract on aluminium sulphate induced alterations in serum lipid profi le of male albino rats, Rattus norvegicus

Abstract: The present study suggests that treatment with Aloe vera a medicinal plant belonging to the family-Liliaceae, used in traditional Indian medicine system and its active constituent Aloin has a positive and therapeutic effect in lowering the lipid profi le level in aluminium sulphate exposed rats for a period of 60 to 90 days. Lipid profi le (total cholesterol, triglyceride, HDL and LDL) levels were found to signifi cantly increased (P<0.05) after treatment of Al 2 (So 4) 3 in Group II compared to normal control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…A number of authors have reported administration of aluminum sulphate mediated toxicity in rats [9,10]. Mahor and Ali [11] suggested that rats received aluminium sulphate in a dose of 98 mg/kg of body weight orally for 30 and 60 days has significantly elevated the normal levels of liver enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors have reported administration of aluminum sulphate mediated toxicity in rats [9,10]. Mahor and Ali [11] suggested that rats received aluminium sulphate in a dose of 98 mg/kg of body weight orally for 30 and 60 days has significantly elevated the normal levels of liver enzymes.…”
Section: Introductionmentioning
confidence: 99%